Transformative Intellectual Discourse and Movement of Ikatan Mahasiswa Muhammadiyah (IMM) - Widodo, Arif (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2017)
Recently, there has been an increasingly concern to completely address social problems particularly those faced by the oppressed people who have no access to economic wealth and have been marginalized by unjust structure at the same time. As an idealistic organization, Muhammadiyah student association (IMM) aspires to be in the frontline of tackling that matter. In dealing with such a multidimensional problem, IMM attempts to adopt multidisciplinary approach proposed by Amin Abdullah and Kuntowijoyo since currently, it has been successfully adopted by many scholars. This paper was intended to enhance the idea of combining natural and social sciences, as well as philosophy and humanities into more transformative and liberal movement in order to solve the exacerbated problems of humanity in recent decades. This purpose can be accomplished through exploring and directing transformative paradigm as proposed by Moslem Abdurrahman, Kuntowijoyo and Omid Safi into a multidisciplinary approach. As a result, intellectual movement can be established by IMM where students from various academic backgroundsâboth natural and social sciencesâmay gather and discuss to bring about the social and structural transformation.